Transcriptomics: An Important Tool in The Analysis of the Skeletal Muscle - Felipe, Gomes Ferreira Padilha (Journal of Skeletal Muscle, 2018)
A review of transcriptomic tools for skeletal muscle research, covering experimental design, data analysis, and applications in physiology and disease.